Research of digestion of cattle manure and chicken dung mixture with iron-based additives - Dauknys, Regimantas; Rokaitė, Agnė (International Conference “Environmental Engineering”, 2026)
This study evaluated the anaerobic co-digestion of cattle manure and chicken dung (70/30% ratio on a DS basis) supplemented with iron-based additives (SBGx, SBGx Plus, and BC. Atox Scon) under continuous mesophilic conditions. Two 16 l reactors were operated with an inoculum-to-substrate ratio of 5:1 (on a VS basis) and a daily loading rate of 0.52 l/d (7–10% DS). The experiment was conducted in two phases: Stage I compared a control to BC. Atox Scon, while Stage II compared SBGx Plus to SBGx. Results indicated that while the additives significantly influenced the initial 15 days of digestion, none enhanced total biogas or methane production relative to the control, which achieved the highest overall yields (190 l CH4/31 d). Although BC. Atox Scon yielded the highest mean methane concentration, it resulted in the lowest cumulative methane volume. All additives markedly reduced H2S levels, with SBGx Plus achieving the most efficient mitigation (mean 1.88 ppm). The study demonstrates that while iron-based additives are highly effective for biogas purification, their impact on total energy yield varies across different experimental stages.